The Effect of Guided Discovery Learning and Scientific Literacy on Senior High School Students Science Process Skills in Newton's Laws - Aslamia, Debby; Astra, I Made; Wibowo, Firmanul Catur (Universitas Lambung Mangkurat, 2025)
The goals of this research are to (1) compare the scientific process abilities of students with high and low science literacy levels in the guided discovery learning group to those of students in the expository group and (2) determine how learning models interact with science literacy to impact science process capabilities. The study used a 2x2 factorial design and was quantitative, using a quasi-experimental methodology. All eleventh graders at IPA MAN 11 in Jakarta were eligible to participate in this research. Utilizing a purposive sampling technique, the sample was derived from two classes: one that was taught using the guided discovery learning model and another that was taught using the expository model. Within each class, there were two subgroups: those with high science literacy and those with low science literacy. Data is gathered using a pre-and post-test approach using instruments such as a science literacy questionnaire and a test of scientific process abilities. According to the study's findings, students in the guided discovery learning group exhibited significantly better science process skills than those in the expository group, regardless of whether their science literacy level was high or low. Scientific process abilities are unaffected by the learning model's connection with scientific literacy. On the other hand, competency in the scientific method is another area in which science literacy helps. The interplay between good scientific literacy and the guided discovery learning paradigm affects students' abilities to carry out the scientific method. When paired with strong scientific literacy, the guided discovery learning methodology may help students become more proficient in the scientific process. This finding indicates that combining discovery-based learning and technology can be an innovative alternative to science learning.